(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2025)
This research aims to understand the relationship between work life balance and employee engagement among married female workers, therefore a quantitative approach is used. The purposive sampling method was used to select respondents as many as 150 married female workers in Bontang City, East Kalimantan. Data were analyzed using the Pearson Product Moment correlation test. This research shows a relationship between work life balance and employee engagement in the medium category, which means that the higher the work life balance applied, the higher the employee attachment to married female workers in Bontang City. The implications of this research are to become a basis for helping create a more inclusive, supportive and sustainable work environment for agencies and married female workers in Bontang City.